Uji Aktivitas Antibakteri Ekstrak Metanol dan Akuades Daun Ganitri (Elaeocarpus ganitrus Roxb.) Terhadap Bakteri Streptococcus mutans - Naelaz Zukhruf Wakhidatul Kiromah; Wahyu Rahmatulloh (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2020)
Streptococcus mutans is responsible for cause the dental caries. The purpose of this research was to test antibacterial activity of Ganitrus leaves. The bacterial activity of methanol and aquadest by disc difusion method with 10; 20; 30; 40; 50 and 100%. The extracts showed that methanol extract had activity with category susceptible at concentration of 50% and 100% against Streptococcus mutans with inhibition zone 16,70 and 17,68 mm respectively. Aquadest extract showed activity with category intermediet of 30% and 100% with inhibition zone 11,04 and 11,39 mm. There is a significant difference in the inhibition zone diameter at each treatment.